2007
DOI: 10.3233/nre-2007-22306
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and autoregulatory physiological dysfunction as a primary characteristic of post concussion syndrome: Implications for treatment

Abstract: Although most patients with concussion recover within days to weeks, a small but significant minority develop persistent signs and symptoms of post-concussion syndrome (PCS). The standard treatments of PCS, rest and cognitive adaptation, have limited effectiveness. PCS patients are advised not to exercise because of the concern for symptom exacerbation. Prolonged rest, however, leads to deconditioning (especially in athletes) and may cause secondary effects including depressive symptoms. Concussion is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(79 citation statements)
references
References 72 publications
2
77
0
Order By: Relevance
“…Our study fits well with the ABCDE (Awakening and Breathing Co-ordination, Delirium monitoring and Exercise/Early mobility) model used in the intensive care setting for prevention of brain dysfunction (Vasilevskis et al 2010). We concur with the general recommendation in clinical practice that concussion patients should rest until they are asymptomatic (Leddy et al 2007), but once they reach this stage we believe that a proper exercise intervention programme should be initiated. Such interventions could provide significant benefits and dramatically reduce patients' recovery period, as seen in our model.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our study fits well with the ABCDE (Awakening and Breathing Co-ordination, Delirium monitoring and Exercise/Early mobility) model used in the intensive care setting for prevention of brain dysfunction (Vasilevskis et al 2010). We concur with the general recommendation in clinical practice that concussion patients should rest until they are asymptomatic (Leddy et al 2007), but once they reach this stage we believe that a proper exercise intervention programme should be initiated. Such interventions could provide significant benefits and dramatically reduce patients' recovery period, as seen in our model.…”
Section: Discussionsupporting
confidence: 83%
“…Although exercise exerts many beneficial effects on the brain, including the promotion of neuronal repair (Vaynman & Gomez-Pinilla, 2005) and inhibition of neuroinflammation (Leem et al 2011), the effects of exercise in animal studies of traumatic brain injury have been controversial (McCrea et al 2009). Moreover, most postconcussion patients are advised not to exercise because of concerns regarding exacerbation of symptoms (Leddy et al 2007). We have shown that exercise improves learning and memory (Huang et al 2006;Liu et al 2009) and enhances neuroprotective effects against brain degeneration (Wu et al , 2011.…”
Section: Introductionmentioning
confidence: 98%
“…Post‐TBI autonomic dysfunction has been proposed as a possible cause for prolonged symptoms of PCS [20]. In studies of moderate to severe TBI, altered ANS regulation is believed to be due to changes in the autonomic centers in the brain and/or an uncoupling of the connections between the central ANS, the arterial baroreceptors, and the heart [21], is proportional to TBI severity, and improves with TBI recovery [21].…”
Section: The Physiology Of Concussionmentioning
confidence: 99%
“…Thus, it is critical to know the time of day when individuals are tested so that any follow-up testing can be carried out at the same time to ensure that the data being collected are physiologically appropriate to compare (Burton et al, 2010;Shaffer et al, 2014). This is especially important when considering concussion as there are changes in circadian rhythm that coincide with the injury (Leddy et al, 2007). Additionally, it is important that any matched control participants being tested against a concussed individual do so at the same time of day.…”
Section: Concussion and Hrvmentioning
confidence: 99%